Influence of dough composition on the formation of processing contaminants in yeast-leavened wheat toasted bread. (15th February 2021) - Belkova, Beverly; Chytilova, Lucie; Kocourek, Vladimir; Slukova, Marcela; Mastovska, Katerina; Kyselka, Jan; Hajslova, Jana
Highlights: Toasting considerably enhanced the formation of acrylamide and 3-MCPD esters. Soy lecithin (1%, w/w) increased 3-MCPD esters in toasted bread. Reducing agents decreased the formation of 3-MCPD esters more than six times. No relationship between recipe and toasting was found for GEs formation. Abstract: The influence of dough composition on acrylamide, 3-monochloropropane-1, 2-diol (3-MCPD) esters, and glycidyl esters (GE) formation during bread toasting was investigated. The doughs differed in added amounts of soy lecithin, salt, and reducing agents (l -cysteine and glutathione). The toasting of bread for 2.5 min considerably enhanced the formation of acrylamide and 3-MCPD esters. The addition of lecithin (1%, w/w) resulted in four times higher content of 3-MCPD esters in toasted bread slices. No distinct relationship between dough composition and GE formation in untoasted and toasted bread was found. The addition of reducing agents (0.05%, w/w ) mitigated during toasting not only the formation of 3-MCPD esters (more than six times) but also the extent of Maillard reaction that resulted in three times lower amounts of acrylamide and predominant formation of alcohol-like compounds. Toasted bread without reducing agents contained typical Maillard reaction compounds such as aldehydes, alkyl pyrazines, and derivatives of furan.